2020
DOI: 10.23960/jpp.v10.i2.202013
|View full text |Cite
|
Sign up to set email alerts
|

Values of Character Education in the Sirih Pinang Symbol: A Cultural Value of Coastal Society

Abstract: Values of Character Education in the Sirih Pinang Symbol: A Cultural Value of Coastal Society. Objective: This research aims to reveal the values of character education contained in the symbol of Sirih Pinang when the people of Lampung on the coast held a Nyambai tradition. Method: This research is a qualitative descriptive study, data collection techniques are conducted through observation, interviews, and documentation studies. Data analysis is done by reducing, display, drawing conclusions and verification.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
1
0
1
Order By: Relevance
“…Berikut dijelaskan mengenai ragam gerak tari dan nilai karakter yang terdapat pada setiap geraknya. Nilai-nilai budaya masyarakat Lampung adat Saibatin tercermin di dalam bentuk-bentuk seni pertunjukan tari, dapat diamati dari bentuk gerak tari, makna gerak tari, simbol-simbol yang digunakan dalam pertunjukan tari (Daryanti, Jazuli, & Florentinus, 2020).…”
Section: Hasil Dan Pembahasanunclassified
“…Berikut dijelaskan mengenai ragam gerak tari dan nilai karakter yang terdapat pada setiap geraknya. Nilai-nilai budaya masyarakat Lampung adat Saibatin tercermin di dalam bentuk-bentuk seni pertunjukan tari, dapat diamati dari bentuk gerak tari, makna gerak tari, simbol-simbol yang digunakan dalam pertunjukan tari (Daryanti, Jazuli, & Florentinus, 2020).…”
Section: Hasil Dan Pembahasanunclassified
“…Several previous studies stated that teaching materials based on local values succeeded in inherent cultural values to students (Daryanti, 2021). This is because, revealed that teaching materials are a collection of knowledge that will be consumed by students through fun learning (Iskandarwassid & Sunendar, 2008;Syaharuddin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%